Vitapods: sustainable portable hydroponic gardens / Leviana Andrew ... [et al.] - Andrew, Leviana; Wan Ibrahim, Wan Muhd Faez; Hassan, Siti Salwa; Mat Yusof, Marlita; Zakariah, Habiel (Universiti Teknologi MARA, Kedah, 2024)
Food insecurity and malnutrition persist as enduring global challenges, exacerbated by limited resources and environmental constraints within underserved communities. VitaPods emerge as an innovative solution—a portable hydroponic gardening system designed to cultivate fresh, nutrient-rich produce in any environment. This article delves into the unique features and societal benefits of VitaPods, highlighting their potential to alleviate food insecurity, enhance nutrition, empower individuals and families, and promote sustainable agriculture. VitaPods incorporate a self-sustaining hydroponic design that uses minimal water and no soil, making them adaptable to diverse settings, including urban areas and regions lacking infrastructure. By facilitating efficient cultivation of vegetables and herbs, VitaPods provide a dependable source of nutritious food, thereby mitigating food malnutrition and bolstering community resilience. Moreover, VitaPods aim to improve nutrition, foster self-sufficiency, and advocate for sustainable agricultural practices. From a commercial standpoint, VitaPods show considerable promise through partnerships with non-profit organizations, governmental initiatives, and social enterprises. Their scalability and positive reception underscore their effectiveness in combating hunger and malnutrition on a global scale. A multifaceted approach ensures widespread accessibility through community gardens and expanded distribution channels, thereby generating revenue to support further growth. Sustainability lies at the core of VitaPods' design and development, emphasizing durability and longevity to minimize environmental impact. By reducing dependence on traditional farming methods, VitaPods contribute to environmental sustainability while addressing nutritional deficiencies. Ultimately, VitaPods represent a transformative solution that integrates technological innovation with social impact, empowering populations and advocating for sustainable food production practices worldwide.